Climate Change and Flood Exposure in Settlements: Spatial Analysis of Geographical and Topographical Factors for Urban Resilience - Zakiah Hidayati; Ikaputra Ikaputra (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2025)
Climate change has increased the frequency and intensity of flood events, posing substantial threats to urban settlements, especially those situated in topographically vulnerable areas. This study investigates the role of geographical and topographical attributes—such as elevation, slope, proximity to water bodies, and landform configuration—in shaping flood exposure. Through a systematic literature review of 31 peer-reviewed articles, the research highlights the physical determinants of flood risk under changing climate conditions. It identifies critical spatial factors contributing to exposure, including natural features (e.g., low-lying coastlines and floodplains) and anthropogenic interventions (e.g., artificial fill, unregulated urban expansion, and inadequate drainage). Case studies from diverse contexts—such as O‘ahu (Hawai‘i), Bekasi (Indonesia), and the Tanaro River Valley (Italy)—demonstrate how these spatial characteristics interact with climate-driven hazards to amplify urban flood risks. Unlike many previous studies that emphasize hazard intensity or socio-economic vulnerability, this research narrows its scope to physical exposure as a foundational dimension of risk. The findings stress the need for spatially grounded planning approaches that integrate topographic analysis and nature-based solutions into disaster risk reduction and urban resilience strategies. By focusing on exposure, this study provides a conceptual contribution to the field of urban climate adaptation, reframing physical geography not as a passive backdrop but as an active and dynamic determinant of vulnerability. This study highlights physical exposure as an active spatial condition, offering a reframed perspective for integrating topographic insight into urban flood resilience planning.